Medical Device Maintenance: Prolonging the Use of Medical Device - Dabadi, Sambardhan; Dhungel, Raju Raj; Gajuryal, Sharad Hari (Annapurna Journal of Health Sciences, 2023)
Procurement and installation of medical device and equipment involves a huge amount of finance in healthcare setting. The timely inspection and maintenance of medical device is as important as its design and development. Timely performed preventive maintenance (PM) prolongs the operative life, reduces the maintenance cost and increases the efficacy of the device. Planned preventive maintenance includes the schedules for inspection and maintenance of device so that any problem can be identified earlier and risk associated with device failure can be minimized.